THE IMPLEMENTATION OF ONLINE DISCUSSION BY USING A LEARNING MANAGEMENT SYSTEM (www.nicenet.org)IN THE LITERATURE COURSE ENGLISH STUDY PROGRAM OF UM METRO - Lilis Sholihah (Premise: Journal of English Education and Applied Linguistics, 2016)
Rapid technological changes, making language learning does not recognize the time and places. This means that language learning can be done everywhere and everytime without face-to-face environment. Teaching and learning process without conducting in a face to face environment are rarely happen. One of the way learning can be doing in an online situation by using internet facilities. Nevertheles, the idea of internet based teaching has been renowned all over the world, at least teachers and lecturers shouls be familiar with it. However, most of the lecturers in Indonesia have not applied  online learning without  because learning with media technology is not yet a common practice. There are several reasons why online learning (internet based teaching) have not been carried out, such as lack of knowledge of lecturers in the use of internet facilities, second, classroom learning is still considered more effective than learning by using internet media. Third, limited internet access at home. Referring to this, the authors felt it was important to conduct research on technology-based learning or  Internet-based teaching. The title of the research is the effectiveness of online discussion and face to face discussion in the Literature class in  English education study program of Muhammadiyah University of Metro. The purpose of this research is to explain the implementation of Online Discussion by using www.nicenet.orgin the Literature course especially Prose subject of English Study Program UM Metro. This study used analysis method by explaining the process of online discussion done by sixth semester students of English department of UM Metro. The result of the study showed that the students could follow the instruction of the course by giving some comments on discussion forum. Based on the questionnaire distributed to the students showed that learning by using online discussion is very fun and can improve students’ writing ability.